Perspectives to Strengthening Competencies of Judges in The Supreme Court of The Republic of Indonesia - Putri, Magya Ramadhania; Hidayah, Zainur; Maharani, Anita (Jurnal Manajemen, 2023)
Judges as court apparatus, play a pivotal role in improving organizational performance and enhancing public trust. They are the sole actor who determines the quality of court decisions. However, the cases in the four courts, namely general, religious, state administrative and military courts seemed to outnumber the judges; hence retaining highly skilled judges to rule and write decisions within the time frame is paramount. Using a stakeholder theory approach, this article explores the competency-based development model for judges carried out by the technical training centre of the Indonesian Supreme Court. The research method was descriptive qualitative, purposive sampling for in-depth interviews. The result revealed that each stakeholder, namely technical training managers, supporting lecturers or trainers, working unit, and the public, showed different perspectives on judges’ competencies, knowledge, skills, and attitude due to different interests. Stakeholders’ views highlighted several points: analytical thinking skill improvement, knowledge application, character building, adaptive skills development and reassignment. This study, therefore, provides a new model of judges’ competencies development that emphasizes a throughout human resources management activity application, starting from carrying out apparatus management strategy as a response to bureaucracy reform, strategic environmental changes, and science and information technology development; applying human resources development strategy with stakeholder participation approach through training and development centre; and creating apparatus reassignment strategy. These three strategies lead to an agile civil apparatus to achieve good governance.